Digital Archives Management System for Archives Security at the Balai Pemberdayaan Industri Persepatuan Indonesia (BPIPI) - Lestanti, Ciptari Queen Rachmad Oktavia; Pribadi, Joni Dwi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to design and implement a digital archive management system using Microsoft Access to support archive handling at the BPIPI. The study was motivated by the institution's continued use of manual archiving, which has led to difficulties in document retrieval, weak classification, and a lack of data security. The system was developed by applying Microsoft Access as the core platform, supported by Visual Basic for Applications (VBA) to handle input validation, login control, and archive retrieval functions. The research employed an action research methodology encompassing planning, action, observation, and reflection stages. System evaluation was conducted using the System Usability Scale (SUS), involving 11 respondents from various work units. The results showed an average SUS score of 80, indicating that the system was